Uncover valuable information and solutions with IDNLearn.com's extensive Q&A platform. Our platform offers reliable and comprehensive answers to help you make informed decisions quickly and easily.
Sagot :
To sketch the graph of the polynomial function [tex]\( p(x) = (3x - 9)(x - 1) \)[/tex], let's break the process down into several steps.
### Step 1: Expand the Polynomial
Firstly, it's useful to expand the polynomial to better understand its components.
[tex]\[ p(x) = (3x - 9)(x - 1) \][/tex]
Using the distributive property, we expand it:
[tex]\[ p(x) = (3x \cdot x) + (3x \cdot -1) + (-9 \cdot x) + (-9 \cdot -1) \][/tex]
[tex]\[ p(x) = 3x^2 - 3x - 9x + 9 \][/tex]
Combining like terms, we get:
[tex]\[ p(x) = 3x^2 - 12x + 9 \][/tex]
### Step 2: Find the [tex]\(x\)[/tex]-Intercepts
The [tex]\( x \)[/tex]-intercepts occur where [tex]\( p(x) = 0 \)[/tex].
Setting the factored form to zero:
[tex]\[ (3x - 9)(x - 1) = 0 \][/tex]
This equation is satisfied when either [tex]\(3x - 9 = 0\)[/tex] or [tex]\(x - 1 = 0\)[/tex].
Solving for [tex]\(x\)[/tex]:
[tex]\[ 3x - 9 = 0 \implies x = 3 \][/tex]
[tex]\[ x - 1 = 0 \implies x = 1 \][/tex]
Thus, the [tex]\( x \)[/tex]-intercepts are at [tex]\( x = 3 \)[/tex] and [tex]\( x = 1 \)[/tex], giving us the points [tex]\((3, 0)\)[/tex] and [tex]\((1, 0)\)[/tex].
### Step 3: Find the [tex]\(y\)[/tex]-Intercept
The [tex]\(y\)[/tex]-intercept is found by evaluating [tex]\( p(x) \)[/tex] at [tex]\( x = 0 \)[/tex].
[tex]\[ p(0) = (3 \cdot 0 - 9)(0 - 1) = (-9)(-1) = 9 \][/tex]
So the [tex]\( y \)[/tex]-intercept is at [tex]\( (0, 9) \)[/tex].
### Step 4: Find the Vertex
The vertex of a parabola [tex]\( y = ax^2 + bx + c \)[/tex] is given by the formula:
[tex]\[ x = -\frac{b}{2a} \][/tex]
For the polynomial [tex]\( 3x^2 - 12x + 9 \)[/tex], we have [tex]\( a = 3 \)[/tex] and [tex]\( b = -12 \)[/tex].
[tex]\[ x_{\text{vertex}} = -\frac{-12}{2 \cdot 3} = \frac{12}{6} = 2 \][/tex]
Now, we substitute [tex]\( x = 2 \)[/tex] back into [tex]\( p(x) \)[/tex] to find the [tex]\( y \)[/tex]-coordinate of the vertex.
[tex]\[ p(2) = 3(2)^2 - 12(2) + 9 = 3 \cdot 4 - 24 + 9 = 12 - 24 + 9 = -3 \][/tex]
So the vertex is at [tex]\( (2, -3) \)[/tex].
### Summary of Key Points
- The [tex]\( x \)[/tex]-intercepts are at [tex]\( (1, 0) \)[/tex] and [tex]\( (3, 0) \)[/tex].
- The [tex]\( y \)[/tex]-intercept is at [tex]\( (0, 9) \)[/tex].
- The vertex is at [tex]\( (2, -3) \)[/tex].
### Sketching the Graph
1. Plot the [tex]\( x \)[/tex]-intercepts [tex]\((1, 0)\)[/tex] and [tex]\((3, 0)\)[/tex].
2. Plot the [tex]\( y \)[/tex]-intercept [tex]\((0, 9)\)[/tex].
3. Plot the vertex [tex]\((2, -3)\)[/tex].
4. Draw the parabola through these points, noting that since [tex]\( a = 3 \)[/tex] (which is positive), the parabola opens upward.
Your sketch will show an upward-opening parabola passing through the critical points, providing a clear visual representation of the polynomial function.
### Step 1: Expand the Polynomial
Firstly, it's useful to expand the polynomial to better understand its components.
[tex]\[ p(x) = (3x - 9)(x - 1) \][/tex]
Using the distributive property, we expand it:
[tex]\[ p(x) = (3x \cdot x) + (3x \cdot -1) + (-9 \cdot x) + (-9 \cdot -1) \][/tex]
[tex]\[ p(x) = 3x^2 - 3x - 9x + 9 \][/tex]
Combining like terms, we get:
[tex]\[ p(x) = 3x^2 - 12x + 9 \][/tex]
### Step 2: Find the [tex]\(x\)[/tex]-Intercepts
The [tex]\( x \)[/tex]-intercepts occur where [tex]\( p(x) = 0 \)[/tex].
Setting the factored form to zero:
[tex]\[ (3x - 9)(x - 1) = 0 \][/tex]
This equation is satisfied when either [tex]\(3x - 9 = 0\)[/tex] or [tex]\(x - 1 = 0\)[/tex].
Solving for [tex]\(x\)[/tex]:
[tex]\[ 3x - 9 = 0 \implies x = 3 \][/tex]
[tex]\[ x - 1 = 0 \implies x = 1 \][/tex]
Thus, the [tex]\( x \)[/tex]-intercepts are at [tex]\( x = 3 \)[/tex] and [tex]\( x = 1 \)[/tex], giving us the points [tex]\((3, 0)\)[/tex] and [tex]\((1, 0)\)[/tex].
### Step 3: Find the [tex]\(y\)[/tex]-Intercept
The [tex]\(y\)[/tex]-intercept is found by evaluating [tex]\( p(x) \)[/tex] at [tex]\( x = 0 \)[/tex].
[tex]\[ p(0) = (3 \cdot 0 - 9)(0 - 1) = (-9)(-1) = 9 \][/tex]
So the [tex]\( y \)[/tex]-intercept is at [tex]\( (0, 9) \)[/tex].
### Step 4: Find the Vertex
The vertex of a parabola [tex]\( y = ax^2 + bx + c \)[/tex] is given by the formula:
[tex]\[ x = -\frac{b}{2a} \][/tex]
For the polynomial [tex]\( 3x^2 - 12x + 9 \)[/tex], we have [tex]\( a = 3 \)[/tex] and [tex]\( b = -12 \)[/tex].
[tex]\[ x_{\text{vertex}} = -\frac{-12}{2 \cdot 3} = \frac{12}{6} = 2 \][/tex]
Now, we substitute [tex]\( x = 2 \)[/tex] back into [tex]\( p(x) \)[/tex] to find the [tex]\( y \)[/tex]-coordinate of the vertex.
[tex]\[ p(2) = 3(2)^2 - 12(2) + 9 = 3 \cdot 4 - 24 + 9 = 12 - 24 + 9 = -3 \][/tex]
So the vertex is at [tex]\( (2, -3) \)[/tex].
### Summary of Key Points
- The [tex]\( x \)[/tex]-intercepts are at [tex]\( (1, 0) \)[/tex] and [tex]\( (3, 0) \)[/tex].
- The [tex]\( y \)[/tex]-intercept is at [tex]\( (0, 9) \)[/tex].
- The vertex is at [tex]\( (2, -3) \)[/tex].
### Sketching the Graph
1. Plot the [tex]\( x \)[/tex]-intercepts [tex]\((1, 0)\)[/tex] and [tex]\((3, 0)\)[/tex].
2. Plot the [tex]\( y \)[/tex]-intercept [tex]\((0, 9)\)[/tex].
3. Plot the vertex [tex]\((2, -3)\)[/tex].
4. Draw the parabola through these points, noting that since [tex]\( a = 3 \)[/tex] (which is positive), the parabola opens upward.
Your sketch will show an upward-opening parabola passing through the critical points, providing a clear visual representation of the polynomial function.
Thank you for participating in our discussion. We value every contribution. Keep sharing knowledge and helping others find the answers they need. Let's create a dynamic and informative learning environment together. Discover insightful answers at IDNLearn.com. We appreciate your visit and look forward to assisting you again.